Arrangement and Implementation of Pancasila Industrial Relations in Company Regulations and Collective Labor Agreements - Bernard Brando Yustisio; Niru Anita Sinaga; Sujono Sujono (Fakultas Hukum Dehasen, 2023)
The affirmation of the constitution means that to take all actions in the realm of industrial relations must be based on the law or the provisions of the applicable labor legislation to provide protection for workers/laborers as also regulated in the Human Rights Act. Therefore, it is interesting to examine how the Pancasila Industrial Relations Norms in Indonesian Labor Legislation and How the Implementation of Pancasila Industrial Relations in Making Company Regulations and Collective Labor Agreements in a Company. To answer these problems, normative legal research methods are used (juridical normative) with a statutory approach, conceptual approach, and comparative approach, using secondary data obtained from primary, secondary and tertiary legal sources. The research found that Pancasila industrial relations norms originated from Pancasila which is a tangle of main basic values is a crystallization of various values that live in society as the soul of the nation (volskgeist) and guiding star (leidstar) in social life, because the main basic value is still very abstract and cannot be legally enforced, or cannot be sanctioned if violated, then as a concretization of these basic values must be outlined in legislation so that it can be enforced and sanctioned if violated and the Implementation of Pancasila Industrial Relations in Making Company Regulations and Collective Labor Agreements in a Company, should involve and accommodate the aspirations of workers through trade unions / workers' representatives in making Company Regulation policies (PP) and Collective Labor Agreements (PKB). Pancasila Industrial Relations is part of contractual relations as a mutual agreement between employers and workers, the achievements and implementation of the agreement should not conflict with Pancasila Industrial Relations and justice.